Evolution and Morphological Shape Ontogeny of the Brown ticks (Acari: Ixodida: Ixodidae: Rhipicephalus) - Bakkes, Deon Kahlil (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.